Stability of vitamin A at critical points in pet-feed manufacturing and during premix storage - Galli, Gabriela Miotto; Andretta, Ines; Martinez, Nicolas; Wernick, Bruno; Shastak, Yauheni; Gordillo, Alvaro; Gobi, Jaqueline (Frontiers in Veterinary Science, 2024)
The objective of this research was to assess and quantify the potential vitamin A losses that occur during the manufacturing of pet feed and premix, as well as during their extended storage periods. This trial was conducted at a commercial feeder mill that utilized a standard commercial dog feed along with a corresponding vitamin-mineral premix. The calculated amount of vitamin A supplemented in the feed, in addition to the endogenous vitamins present in the ingredients, was adjusted to 18,000 IU/kg of feed. Five 500 g feed samples were collected at each of the predefined critical points throughout the manufacturing process (after mixing, milling, preconditioner, and extrusion/drying processes) to verify the stability of vitamin A during feed production. Additionally, various samples were collected at regular intervals of 30, 60, 90, 120, and 180 days during the storage of the premix to assess the stability of vitamin A. Vitamin A analyses in the samples were performed using high-performance liquid chromatography. The variables were assessed for normality using the Shapiro-Wilk test, followed by analysis of variance (ANOVA) and Tukey’s test to compare the differences between the manufacturing process and premix shelf life. The statistical significance was set at 95%. The vitamin losses during the pre-conditioning process were 26%, and during the extrusion-drying processes, the losses were 34% when compared to the initial analyzed value. However, no differences were observed in other processes. There were no significant differences observed in recovered vitamin levels in the premix during its shelf-life (P=0.484). The study indicated that the primary vitamin A losses in pet feed manufacturing processes occur during the pre-conditioning and drying/extrusion steps. However, it is worth noting that no significant losses of vitamin A were found during the premix storage phase.